2016
DOI: 10.1017/dmp.2015.171
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Accuracy of Three Pediatric Disaster Triage Strategies: A Simulation-Based Investigation

Abstract: Our simulation-based comparison suggested that JumpSTART triage outperforms both Smart and CDM. JumpSTART outperformed Smart for RED patients and CDM for BLACK patients. For YELLOW patients, JumpSTART yielded more accurate triage results than did Smart triage or CDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…The result showed that the highest level of accuracy of the START system was recorded at 94.2% when this model was applied to the medical record data of MCI train victims in Italy. Whereas in another MCI victim medical record analysis from the USA, it was found that the accuracy of the START system was only 44% (Badiali et al, 2017;Cicero et al, 2016;Cone et al, 2011;Jones et al, 2014;Kahn et al, 2009;Lee et al, 2016;Lerner et al, 2010;Silvestri et al, 2017). This indicates that the START triage system is inconsistent in terms of accuracy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The result showed that the highest level of accuracy of the START system was recorded at 94.2% when this model was applied to the medical record data of MCI train victims in Italy. Whereas in another MCI victim medical record analysis from the USA, it was found that the accuracy of the START system was only 44% (Badiali et al, 2017;Cicero et al, 2016;Cone et al, 2011;Jones et al, 2014;Kahn et al, 2009;Lee et al, 2016;Lerner et al, 2010;Silvestri et al, 2017). This indicates that the START triage system is inconsistent in terms of accuracy.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, in a simulated paediatric MCI scenario, medical students achieved a jumpSTART accuracy of 85.7% (Claudius et al, 2015). Moreover, Cicero et al (2016), in their simulated MCIs study among medical students, found that jumpSTART was more accurate than other disaster and MCI triage systems. On the other hand, three mass casualty simulation-based studies identified the range of accuracy of the SALT triage system to be between 70% and 83%.…”
Section: Theme 1: the Accuracy Of Salt And Start Triage Systemsmentioning
confidence: 97%
“…Few bespoke paediatric triage tools have been derived and there is minimal data from external validations to support the use of one over another on the basis of performance characteristics. 2,15,21-23 Whilst previous studies have compared triage tool performance using either mortality or ISS, neither of these are likely to extrapolate well to the acuity of the patient whilst in the pre-hospital setting. 2-4 In a major incident, the purpose of triage is to prioritise those patients who may benefit from life-saving interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of this study was to compare triage outcomes of Simple Triage and Rapid Treatment (START 2,16 ), modified START as used by the Fire Department of New York (FDNY; New York USA), 5,9 and CareFlight 9,12 in patients under 16 years of age (Figure 1) to an outcomes-based gold standard using the COT. The secondary outcomes were to determine sensitivity, specificity, under-triage, and over-triage at each level for each MCI triage algorithm along with the overall accuracy of the MCI algorithm.…”
Section: Introductionmentioning
confidence: 99%